Universities, Academics and Spin Out Companies: Lessons from Imperial - Birley, Sue (Senate Hall, 2003)
This paper explores the issues faced by organizations when attempting to commercialize their Intellectual Property. It draws upon the particular experiences of Imperial College of Science, Technology and Medicine, the largest university in the UK in terms of research revenue and with the largest medical school. Because of the nature of the academic system, and the concept of academic freedom, these issues are more complicated and more difficult to solve in a university than anywhere else. Nevertheless, the lessons are common to all types of organization. The paper argues that there are three types of spinout, which are called orthodox, hybrid and technology, with the hybrid being the most common and most complicated within the university context. The issues explored include establishing proof of both technology and market concept, the potential roles of the inventor, the multiple stakeholders, the various conflicts of interest, the allocation of equity, the assigning of Intellectual Property, and the resultant need to provide warranties.
Keywords: spinouts|universities|intellectual property|entrepreneurship